PENDAMPINGAN PADA PENGEMBANGAN BISNIS PADA PENGOLAHAN MAKANAN KRUPUK REMIS UMK KOJA DI DESA KONGSI JAYA KABUPATEN INDRAMAYU - Agus Yudianto; Nana Supriatna Sonjaya (BUDIMAS : JURNAL PENGABDIAN MASYARAKAT, 2023)
In general, the target to be achieved for UKM Koja IM is the creation of UKM based on digital technology so that it can be known to the wider community and increase the amount of productivity which of course will affect the number of human resources. To develop SMEs involves various parties. SMEs themselves initially started from home industrial activities and those most dominantly involved were the SME owners themselves. SME owners who organize and manage the production process. In general, the target to be achieved for UKM Koja IM is the creation of UKM based on digital technology so that it can be known to the wider community and increase the amount of productivity which of course will affect the number of human resources. a. In production activities, we help with the process of mixing the raw materials together, mixing the dough, steaming the cracker dough, drying the crackers, frying the crackers, and packaging the crackers. In marketing activities, we expand our marketing by promoting through online social media such as Instagram and to increase sales we include products in e-commerce such as shops. Creating packaging innovations that are more economical in size, by repackaging the packaging so that it can attract buyers for more economical sizes and designing packaging by providing labels along with the composition contained in the production of mussel crackers. The aim is to attract buyers' attention by repackaging the packaging. Making financial reports, we analyzed the financial reports of Koja Im producing mussel crackers.